Selenium Biofortification in Radish Enhances Nutritional Quality via Accumulation of Methyl-Selenocysteine and Promotion of Transcripts and Metabolites Related to Glucosinolates, Phenolics, and Amino Acids - Schiavon, Michela; Berto, Chiara; Malagoli, Mario; Trentin, Annarita; Sambo, Paolo; Dall'Acqua, Stefano; Pilon-Smits, Elizabeth A. H. (Frontiers in Plant Science, 2016)
Two selenium (Se) fertilization methods were tested for their effects on levels of anticarcinogenic selenocompounds in radish (Raphanus sativus), as well as other nutraceuticals. First, radish was grown on soil and foliar selenate applied 7d before harvest at 0, 5, 10 and 20 mg Se per plant. Selenium levels were up to 1,200 mg Se/kg DW in leaves and 120 mg Se/kg DW in roots. The thiols cysteine and glutathione were present at 2-3 fold higher levels in roots of Se treated plants, and total glucosinolate levels were 35% higher, due to increases in glucoraphanin. The only seleno-aminoacid detected in Se treated plants was Se-methyl-SeCys (100 mg/kg FW in leaves, 33 mg/kg FW in roots). The levels of phenolic aminoacids increased with selenate treatment, as did root total nitrogen and protein content, while the level of several polyphenols decreased. Second, radish was grown in hydroponics and supplied with 0, 5, 10, 20, or 40 microM selenate for one week. Selenate treatment led to a 20-30% increase in biomass. Selenium concentration was 242 mg Se/kg DW in leaves and 85 mg Se/kg DW in roots. Cysteine levels decreased with Se in leaves but increased in roots; glutatione levels decreased in both. Total glucosinolate levels in leaves decreased with Se treatment due to repression of genes involved in glucosinolates metabolism. Se-methyl-SeCys concentration ranged from 7-15 mg/kg FW. Aminoacid concentration increased with Se treatment in leaves but decreased in roots. Roots of Se treated plants contained elevated transcript levels of sulfate transporters (Sultr) and ATP sulfurylase, a key enzyme of S/Se assimilation. No effects on polyphenols were observed. In conclusion, Se biofortification of radish roots may be achieved via foliar spray or hydroponic supply. One to ten radishes could fulfill the daily human requirement (70 microg) after a single foliar spray of 5 mg selenate per plant or one week of 5-10 microM selenate supply in hydroponics. The radishes metabolized selenate to the anticarcinogenic compound Se-methyl-selenocysteine. Selenate treatment enhanced levels of other nutraceuticals in radish roots, including glucoraphanin. Therefore, Se biofortification can produce plants with superior health benefits.